Pt nanoparticles decorated TiO2 nanotubes for the reduction of olefins - Anitha, V. C.; Goswami, Anandarup; Sopha, Hanna; Nandan, Devaki; Gawande, Manoj B.; Cepe, Klara; Ng, Siow Woon; Zboril, Radek; Macak, Jan M. (Applied Materials Today, 2018)
High surface area TiO2 nanotubes (TNTs) were used as a catalyst support for well dispersed, stable and ultra-small (3–5 nm) Pt nanoparticles (Pt@TNTs) for the reduction of olefins. Pt@TNT catalyst was synthesized by a simple soaking of anodized TNTs in the chloroplatinic (H2PtCl6) acid solution. Various techniques such as XRD, SEM, TEM, and XPS were used to characterize the materials and its catalytic property for the olefin reduction has been described along with a proposed mechanism. The Pt@TNT catalyst showed moderate to high catalytic conversions of styrene and its derivative to ethyl benzene-based products using hydrazine hydrate as a reducing agent. An excellent catalytic activity along with high product selectivity was achieved using low amount (10 mg) of Pt@TNT catalyst containing ∼2.2 wt.% Pt and short reaction time (45 min).
CRIS-Team Scopus Importer:2022-11-02
Keywords: Anodization; Catalysis; Pt nanoparticles; Reduction of olefins; TiO